Self-assembly of Fe nanocluster arrays on templated surfaces - LUEBBEN, OLAF; SHVETS, IGOR; MURPHY, BARRY (My University, 2012)
The growth of Fe nanoclusters on the Ge(001) and MoO2/Mo(110) surfaces has been studied using low-temperature scanning tunneling microscopy (STM) and X-ray magnetic circular dichroism (XMCD). STM results indicate that at low coverage Fe atoms self-assemble on both surfaces into well-separated nanoclusters, which nucleate at equivalent surface sites. Their size, shape, and the observed spatial separation are dictated by the substrate and depend on preparation conditions. Annealing the Fe nanoclusters on Ge(001) at 420K leads to the formation of linear nanocluster arrays, which follow the Ge dimer rows of the substrate, due to cluster mobility at such temperature. In turn, linear Fe nanocluster arrays are formed on the MoO2/Mo(110) surface at room temperature at a surface coverage greater than 0.5 monolayer. This is due to the more pronounced row pattern of the MoO2/Mo(110) surface compared to Ge(001). These nanocluster arrays follow the direction of the oxide rows of the strained MoO2/Mo(110) surface. The Fe nanoclusters formed on both surfaces show a superparamagnetic behavior as measured by XMCD.
PUBLISHED
Keywords: Fe nanocluster arrays